ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT DALAM MEMANFAATKAN LAYANAN PEGADAIAN DI ERA DIGITAL - Alifah, Alifah Nahdah; Putri Nurhajizah Pane; Nurul Miftahul Jannah; Dinda Karunia Putri (Cattleya Darmaya Fortuna, 2025)
Digital transformation has brought significant changes in various sectors, including the pawnshop industry. This research aims to analyze the factors that influence people's interest in utilizing pawnshop services in the digital era. The factors analyzed include ease of access to services, trust in pawnshop institutions, understanding of technology, and digital-based service innovation. The research method used is a quantitative approach with data collection techniques in the form of surveys distributed to the user community and potential users of digital pawnshop services. The research results show that ease of access and trust are the main factors that drive public interest. Apart from that, service innovation and understanding of technology also play an important role in influencing people's decisions to use pawnshop services. This study provides recommendations for pawnshop institutions to continue to improve the quality of digital services and build trust through transparency and data security to increase public interest.